THE ROLE OF THE IMPLEMENTATION OF THE GREEN BANKING CONCEPT ON SUSTAINABILITY PERFORMANCE - Estu Widarwati; Amelia Eka Wanda (STIESA Press, 2023)
Indonesia's improving economy has created enthusiasm for entrepreneurs to run their businesses in Indonesia. This can be seen from Indonesia's economic growth in the last 5 years, namely from 2016 to 2019 which was good, but the Indonesian economy in 2020 contracted by 2.07% because in 2021 it was affected by the pandemic so that it is expected that the Indonesian economy will improve again and return to normal. The national economic recovery has greatly contributed to supporting the improvement of banking performance after the Covid-19 pandemic, especially in Indonesia, this can be seen from the growing credit distribution and public deposit funds. Research trends on the relationship between sustainability and green banking are starting to remember in Indonesia, along with the increasing number of companies, both financial and non-financial, that publish sustainability reports. The object of this study is to analyze the effect of the application of the green banking concept on sustainability, The type of data used in this study is quantitative data, the research sample is 26 banks that finance PROPER companies and those who publish sustainability reports and annual reports for the 2020-2022 observation period. The results of the study found that Green Banking practices have a positive and significant effect on Sustainability Performance. This shows that the better banks implement the concept of green banking can be one of the considerations of stakeholders to make financial decisions. The results of this research can be used as a benchmark for banks in order to further increase their attention to sustainability disclosure so as to create sustainable economic development or contribute to the SDGs program, especially in Indonesia, this of course can be used as additional information as consideration for investors and certain parties in analyzing and deciding their financial decisions.